Knowing better: conspiratorial wellness, national bodies, and global plots in Turkish popular media - Karaosmanoglu, Kerem (ROUTLEDGE JOURNALS, TAYLOR & FRANCIS LTD, 2026)
This article examines conspiratorial accounts of health, nutrition, and wellness in Turkey, arguing that they are best understood not as marginal or stigmatized forms of knowledge, but as culturally embedded and nationally resonant modes of interpretation circulating within popular media. Drawing on a thematic analysis of popular books, newspaper columns, television programs, and YouTube content produced between 2018 and 2025, the article challenges analytical models that insufficiently capture the specificity of the Turkish context. In Turkey, conspiratorial claims about health and nutrition are not confined to the periphery but occupy visible and often authoritative positions in popular culture. These claims draw on nationalist, religious, scientific, and pseudo-scientific registers, mobilizing familiar cultural symbols and metaphors to legitimize alternative forms of knowledge. By foregrounding popular culture and nationally grounded frameworks, the article contributes to broader debates on conspiracy theories and knowledge production beyond approaches centred on marginalization and epistemic exclusion.
Keywords: Wellness; health; media; conspiracy theory; Turkey; BELIEFS; Area Studies